Onset and evolution of anxiety in Parkinson's disease. (29th December 2016) - Zhu, K.; van Hilten, J. J.; Marinus, J.
Abstract : Background and purpose: Anxiety is common in Parkinson's disease (PD) and has a great influence on quality of life. However, little is known about risk factors for development of anxiety in PD. We investigated which factors were associated with longitudinal changes in severity of anxiety symptoms and development of future anxiety in patients who were not anxious at baseline. Methods: Analyses were performed on data of the PROfiling PARKinson's disease (PROPARK) cohort, a 5‐year hospital‐based longitudinal cohort of over 400 patients with PD who have been examined annually. Linear mixed models were used to identify factors associated with longitudinal changes in Hospital Anxiety and Depression Scale – Anxiety (HADS‐A) scores. Survival analysis using data of patients who were not anxious at baseline was performed to identify predictors of future anxiety (i.e. HADS‐A ≥ 11). Results: Of 409 patients who were included at baseline, 67 (16%) had anxiety, whereas 64 (19%) of the remaining 342 non‐anxious patients developed anxiety after a mean (SD) follow‐up of 2.6 (1.3) years. Seventy percent of the patients with anxiety were also depressed. Female gender, cognitive impairment, depressive symptoms, dysautonomia, insomnia and excessive daytime sleepiness (EDS) at baseline were associated with higher HADS‐A scores over time and, except for female gender and EDS, all of these variables were independent predictors of development of anxiety in patients who were not anxious at baseline. Conclusions: Anxiety is highly prevalent in PD. Higher anxiety scores over time and future development of anxiety are associated with female gender, cognitive impairment, autonomic dysfunction, insomnia and EDS. Anxiety and depression usually coexist and share similar determinants, suggesting a common pathophysiological mechanism.